Karakteristik Ibu yang Memberikan Susu Formula pada Bayi di RB Setia RUmanda Jakarta-Timur - Cita, Yatnita Parama; Ismiati, (Jurnal Keperawatan Soedirman, 2008)
This research is about the characteristics of the mothers who give formula milk to their 0-6 months-old infants at Setia Rumanda Hospital in East Jakarta. The research used cross- sectional method to identify the relation between the independent variables and the dependent variable. The independent variables were age, education, occupation, and the residences, while the dependent variable was the administering of formula milk. The results show that the number of the mothers giving formula milk to their 0-6 months-old infants (76%) is greater than the number of the breast-feeding mother (29%). The percentage distributions of the mother who give formula milk are: 62% for the mother with age under 25 years old, 51% for the low-education mothers, 62% for the working mother, and 57% for the mothers living in urban areas. The conclusions of this research is that the number of mothers who give formula milk is greater than the number of breast-feeding mothers and the characteristics of mothers who give formula milk are under 25 years old, low education, working and living in urban areas.